THE EFFECTIVENESS OF COGNITIVE BEHAVIOR THERAPY FOR BORDERLINE PERSONALITY DISORDER: RESULTS FROM THE BORDERLINE PERSONALITY DISORDER STUDY OF COGNITIVE THERAPY (BOSCOT) TRIAL - Davidson, Kate (2006)
The outcome of a randomized controlled trial of cognitive behavior therapy in addition to treatment as usual (CBT plus TAU) compared with TAU alone (TAU) in one hundred and six participants meeting diagnostic criteria for borderline personality disorder is described. We anticipated that CBT plus TAU would decrease the number of participants with in-patient psychiatric hospitalizations or accident and emergency room contact or suicidal acts over twelve months treatment and twelve months follow-up, compared with TAU. We also anticipated that CBT plus TAU would lead to improvement in a range of secondary outcomes of mental health and social functioning compared to TAU. Of the 106 participants randomized, follow-up data on 102 (96%) was obtained at two years. Those randomized to CBT were offered an average of 27 sessions over 12 months and attended on average 16 (range 0 to 35). We found that the global odds ratio of a participant in the CBT plus TAU group compared with the TAU alone group having any of the outcomes of a suicidal act, in-patient hospitalization, or accident and emergency contact in the 24 months following randomization was 0.86 (95% confidence interval [CI] 0.45 to 1.66, p = 0.66). The corresponding global odds ratio, excluding accident and emergency room contact, was 0.75 (95% CI 0.37 to 1.54, p = 0.44). In terms of the number of suicidal acts, there was a significant reduction over the two years in favor of CBT plus TAU over TAU, with a mean difference of −0.91 (95% CI −1.67 to −0.15, p = 0.020). Across both treatment arms there was gradual and sustained improvement in both primary and secondary outcomes, with evidence of benefit for the addition of CBT on the positive symptom distress index at one year, and on state anxiety, dysfunctional beliefs and the quantity of suicidal acts at two year follow-up. CBT can deliver clinically important changes in relatively few clinical sessions in real clinical settings.